β-Galactosidases from a Sequence-Based Metagenome: Cloning, Expression, Purification and Characterization - Eberhardt, María Florencia; Irazoqui, Jose Matias; Amadio, Ariel (MDPI, 2021)
Stabilization ponds are a common treatment technology for wastewater generated by dairy industries. Large proportions of cheese whey are thrown into these ponds, creating an environmental problem because of the large volume produced and the high biological and chemical oxygen demands. Due to its composition, mainly lactose and proteins, it can be considered as a raw material for value-added products, through physicochemical or enzymatic treatments. β-Galactosidases (EC 3.2.1.23) are lactose modifying enzymes that can transform lactose in free monomers, glucose and galactose, or galactooligosacharides. Here, the identification of novel genes encoding β-galactosidases, identified via whole-genome shotgun sequencing of the metagenome of dairy industries stabilization ponds is reported. The genes were selected based on the conservation of catalytic domains, comparing against the CAZy database, and focusing on families with β-galactosidases activity (GH1, GH2 and GH42). A total of 394 candidate genes were found, all belonging to bacterial species. From these candidates, 12 were selected to be cloned and expressed. A total of six enzymes were expressed, and five cleaved efficiently ortho-nitrophenyl-β-galactoside and lactose. The activity levels of one of these novel β-galactosidase was higher than other enzymes reported from functional metagenomics screening and higher than the only enzyme reported from sequence-based metagenomics. A group of novel mesophilic β-galactosidases from diary stabilization ponds’ metagenomes was successfully identified, cloned and expressed. These novel enzymes provide alternatives for the production of value-added products from dairy industries’ by-products.